On Different Sides: Investigating the Persuasive Effects of Anger Expression in Political News Messages. Issue 4 (19th November 2018) - Van 't Riet, Jonathan; Schaap, Gabi; Kleemans, Mariska; Veling, Harm; Lecheler, Sophie
Abstract : Anger expression is increasingly prevalent in political news messages. However, the persuasive effects of expressing anger in a political context have received scant attention from researchers. We conducted two experiments to investigate the hypothesis that anger expression is detrimental to persuasion because it runs counter to well‐established social norms for the polite expression of opinions. We created political news messages including a persuasive appeal by a politician that was supported either with an expression of anger or with an expression of nonemotional disagreement. The results of Experiment 1 (N = 120) showed that anger messages were perceived as less appropriate than control messages, and that politicians expressing anger were perceived as less likable and less competent than politicians who disagreed in nonemotional terms. In Experiment 2 (N = 1, 005), the negative effects of anger expression on perceived likability and competence were replicated. Also in line with Experiment 1, anger messages were perceived as less appropriate, but this time only for those with negative a priori attitudes toward the advocated position. In contrast, those with positive a priori positions toward the advocated position perceived anger messages as more appropriate than the control messages.